Man MANAJEMEN PENDIDIKAN KARAKTER KEPALA MADRASAH UNTUK MENINGKATKAN MUTU GURU DI MTS NURUL IMAN CIBADUYUT KOTA BANDUNG - Enjang Sunandar (Pergunu Jawa Barat, 2023)
ABSTRAC This study aims to determine the planning character education carried out by the head of the madrasa to improve the quality of teachers in MTs. Nurul Iman Cibaduyut, to find out the form of the organization carried out by the head of the Madrasah MTs Nurul Iman Cibaduyut in fostering teacher performance, to find out the implementation of character education to improve the quality of teachers carried out by the head of the Madrasah MTs Nurul Iman Bandung, to determine the supervision of improving the quality of teachers carried out by the head Madrasah, MTs Nurul Iman, Cibaduyut, Bandung. The approach and method of this research are qualitative, namely research that focuses on empirical phenomena naturally and analyzed using scientific logic of thinking. The data collection techniques in this study were obtained through observation, interviews, documentation, and triangulation. Data analysis was carried out by reducing data, presenting data, and verifying data, and then formulating conclusions from the results of the research conducted Keywords: Management, character education, madrasa principals, teacher quality